Suprabasal BCL-2 expression does not sensitize to chemically-induced skin cancer in transgenic Mice - Schenkel, Johannes; Weiher, Hans; Fürstenberger, Gerhard; Jäger, Richard (Anticancer research, 2008)
Background: BCL-2 overexpression is frequently detected in nonmelanoma skin cancer. In normal skin, BCL-2 expression is restricted to the basal cell layer and the hair follicle bulge. Both contain stem cells targeted by carcinogens upon initiation of mouse skin carcinogenesis. It is unknown whether the anti-apoptotic activity of BCL-2 is involved in the susceptibility of this cell type to malignant transformation. If so, extending the pool of BCL-2-expressing cells to suprabasal skin layers should increase the likelihood of skin tumour formation. Materials and Methods: To resolve this issue, we generated a novel transgenic mouse line overexpressing BCL-2 in suprabasal layers of the epidermis. The influence of suprabasal BCL-2 on tumour formation was then tested by chemically inducing skin cancer using the two-stage initiation-promotion protocol. Results: Bcl-2 expression neither influenced the incidence nor the multiplicity of papillomas upon chemical tumour induction with 7,12-dimethylbenz[a]anthracene (DMBA) and 12-O-tetradeca-noylphorbol-13-acetate (TPA), nor their progression to carcinomas. Conclusion: Suprabasal expression of BCL-2 in skin does not increase the formation of papillomas or their malignant progression to squamous cell carcinomas in two-stage mouse skin carcinogenesis.